Factors Determinant Anemia Events in Pregnant Woman in Puskesmas Pesantren I Kediri City - Ira Nurdiana; Nurwijayanti Nurwijayanti; Nurdina Nurdina (Journal for Quality in Public Health, 2018)
Anemia of pregnant women has an impact on the rate of morbidity and maternal mortality, increased morbidity and fetal mortality, and increased risk of LBW. The incidence of anemia is influenced by various factors, including diet, taboo food knowledge, and compliance of Fe tablets. The purpose of this study is to analyze the effect of anemia on pregnant women at Pesantren 1 Health Center of Kediri. The research design used is quantitative research using cross sectional approach. The sampling technique used was simple random sampling with sample of 63 respondents of pregnant women at Pesantren 1 Health Center of Kediri. Data analysis technique used logistic regression test. The result of research showed that from 63 respondents, 32 (50,8%) respondents had bad eating pattern having anemia, as many as 25 (39,7%) respondents had poor taboo knowledge, 46%) respondents are less adherent in consuming Fe tablet so that anemia. The results of analysis using logistic regression test showed significance value of 0.000 <(α = 0.05), meaning H0 rejected and H1 accepted, this means that there is influence of diet, taboo food knowledge, compliance drinking Fe tablet with the incidence of anemia. The most dominant factor affecting the incidence of anemia is adherence (α = 0,000 OR = 45,379). Diet, taboo food knowledge and adherence affects the incidence of anemia by 91% and the incidence of anemia in pregnant women is affected by other factors by 9%. Pregnant women who have poor adherence to consuming Fe tablets have anemia. One of the efforts to reduce anemia is with a good diet, increased knowledge of pregnant women and motivate mothers to obediently take tablets.